Ethiopia's Legal Response to Kidnapping: Gaps and Challenges - Messay Asgedom Gobena (Mizan law review, 2025)
Kidnapping is surging in Ethiopia. Cases of severe kidnapping that eventually resulted in the death of the victims and/or exorbitant ransom demands, reaching millions of birrs, are documented. Ethiopians are paying a terrible price for kidnappers. The more kidnappers gain ground and the menace spreads, the greater risk it poses to society, especially by threatening existing societal bonds and solidarity. The dreadfulness of this crime may have lasting impacts on survivors and their relatives. Thus, combating kidnapping should be a top priority for the Ethiopian state. This article examines the legal landscape of kidnapping in Ethiopia. The researcher adopts the rational choice theory of crime to examine the adequacy of Ethiopia’s penal statutes for the prevention and suppression of kidnapping. It uncovers that Ethiopia’s Criminal Code criminalizes illegal restraints and abduction, including political abduction. The anti-terrorism law of the country also criminalizes hostage-taking or kidnapping. Despite these legal provisions, the criminalization of kidnapping in Ethiopia is accompanied by conceptual vagueness and legal gaps that eventually become a challenge for the prevention and suppression of kidnapping.